Risk factors for dental caries in children with developmental disabilities - Ana Paula Vasques Sales BRAÚNA; Mauro Henrique Nogueira Guimarães de ABREU; Vera Lúcia Silva RESENDE; Lia Silva de CASTILHO (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of the present study was to investigate risk factors for dental caries in children with developmental disabilities who were treated at a clinical reference service for patients with special needs in Belo Horizonte, MG, Brazil. This is a retrospective cohort study that evaluated 401 dental charts of individuals without dental caries or restorations in their first dental appointment. The dependent variable was the time of occurrence of new dental caries or restorations and was measured in months. Gender, age, International Code of Diseases (ICD), mother´s education, sugar consumption, use of fluoride toothpaste, oral hygiene, mouth breathing, reports of xerostomia, gingival status, use of psychotropic or asthma drugs, and history of asthma were covariates. The Cox proportional hazards regression model was used to estimate the raw and adjusted hazard ratios and their respective 95% confidence intervals. The average time that individuals remained free of dental caries/restoration was equal to 107.46 months (95%CI 95.41 to 119.51), with a median of caries-free children up to 94 months. For each point increase in the scale of sucrose consumption, the increase in caries risk was 1.07 (95%CI 1.01 to 1.15). Sucrose consumption was the only risk factor for dental caries found in this group of individuals with developmental disabilities.